Carotid intima media thickness in type 2 diabetes mellitus with ischemic stroke - Sunil Kumar Kota (Indian Journal of Endocrinology and Metabolism, 2013)
Background: Diabetes mellitus is associated with high cardiovascular risk. Carotid intima media thickness (CIMT) is used commonly as a noninvasive test for the assessment of degree of atherosclerosis. The objective of this study was to find out the cut-off point for CIMT for ischemic stroke in patients with type 2 diabetes mellitus (T2DM) and to correlate CIMT with various parameters like smoking, hypertension, lipid profile and duration of T2DM. Materials and Methods: A total of 80 subjects in the age group of 30-75 years (M:F = 57:23) were selected and divided into three groups, i.e. diabetes with ischemic stroke, diabetes and healthy subjects. All the participants were subjected to B-mode ultrasonography of both common carotid arteries to determine CIMT, along with history taking, physical examination and routine laboratory investigations including included fasting and 2-hour postprandial blood sugar, blood urea, serum creatinine, lipid profile, glycated hemoglobin, and microalbuminuria. Results: Patients with T2DM with or without ischemic stroke were found to have significantly higher prevalence of increased CIMT and a value greater than 0.8 mm was found to be associated with the occurrence of stroke. The mean carotid IMT of the group as a whole was 0.840 ± 0.2 mm. The mean carotid IMT was not significantly different between T2DM patients with or without ischemic stroke (1.06 ± 0.2 vs. 0.97 ± 0.26 mm, P = 0.08). However, the mean CIMT was significantly higher in diabetic subjects compared to healthy subjects (1.01 ± 0.28 mm vs. 0.73 ± 0.08, P = 0.006). Other parameters like higher age, smoking, hypertension, hyperlipidemia, low HDL cholesterol, the glycemic parameters and the duration of diabetes were independently and significantly related to CIMT. Conclusion: A high CIMT is a surrogate and reliable marker of higher risk of ischemic stroke amongst type 2 diabetic patients. Our study demonstrates the utility of carotid IMT as a simple non-invasive screening test for the assessment of atherosclerosis risk/prognosis in type 2 diabetics.